A Concise Approach for Producing Optically Pure Carboxylic Acid Segments for the Synthesis of Bicyclic Depsipeptide Histone Deacetylase Inhibitors - Narita, Koichi; Sayar, Noel; Saijo, Ken; Ishioka, Chikashi; Katoh, Tadashi (Synthesis, 2019)
Optically pure carboxylic acid segments, which are common key intermediates for the synthesis of naturally occurring bicyclic depsipeptide histone deacetylase inhibitors, have been produced efficiently. The method features the chromatographic separation of two diastereomers, which were formed by direct amide condensation of racemic (3RS,4E)-3-hydroxy-7-mercaptohept-4-enoic acid (rac-Hmh) with chiral amino acids. This approach offers a reliable and practical method for producing optically pure carboxylic acid segments, which can facilitate easier access to important anticancer agents derived from them.
Keywords: synthetic intermediate; histone deacetylase inhibitor; natural product; bicyclic depsipeptide; total synthesis